THE IMPORTANCE OF TOURISM IN UZBEKISTAN (Modern education and development, 2025)
This article explores the significance of tourism in Uzbekistan, highlighting its economic, cultural, and social impacts. By analyzing existing literature, employing qualitative and quantitative methods, and discussing findings, the article underscores tourism's role in driving economic growth, preserving cultural heritage, and fostering international goodwill. The study provides recommendations for sustainable tourism development to maximize benefits for Uzbekistan's economy and society.